Genetic Diversity, QTL Mapping, and Marker-Assisted Selection Technology in Cotton (Gossypium spp.) - Kushanov, Fakhriddin N.; Turaev, Ozod S.; Ernazarova, Dilrabo K.; Gapparov, Bunyod M.; Oripova, Barno B.; Kudratova, Mukhlisa K.; Rafieva, Feruza U.; Khalikov, Kuvandik K.; Erjigitov, Doston Sh.; Khidirov, Mukhammad T.; Kholova, Madina D.; Khusenov, Naim N.; et al. (Frontiers in Plant Science, 2021)
Cotton genetic resources contain diverse economically important traits that can be used widely in breeding approaches to create of high-yielding elite cultivars with superior fiber quality and adapted to biotic and abiotic stresses. Nevertheless, the creation of new cultivars using conventional breeding methods is limited by the cost and proved to be time consuming process, also requires a space to make field observations and measurements. Decoding genomes of cotton species greatly facilitated generating large-scale high-throughput DNA markers and identification of QTLs that allows confirmation of candidate genes, and use them in marker-assisted selection (MAS)-based breeding programs. With the advances of quantitative trait loci (QTL) mapping and genome-wide-association study approaches, DNA markers associated with valuable traits significantly accelerate breeding processes by replacing the selection with a phenotype to the selection at the DNA or gene level. In this review, we discuss the evolution and genetic diversity of cotton Gossypium genus, molecular markers and their types, genetic mapping and QTL analysis, application, and perspectives of MAS-based approaches in cotton breeding.